Multilateral trading system and regional economic integrations - Savić Biljana (Međunarodni Problemi)
Development in recent years suggets that Regional Trade Agreements have become a very prominent feature of the Multilateral Trading System and an important trade policy instrument for WTO Members. Regional agreements can play an important role in promoting trade and in fostering economic development by increasing trade and FDI flows, and by integrating developing countries into the world economy. However, the proliferation of regional agreements and the development of complex network of preferential trade relations known as the “spaghetti bowl” phenomenon leads to trade diversion which reduce economic efficiency. There is the need to multilateralize regionalism. WTO rules could and should be modified to ensure that regional agreements are designed and implemented so to complement the multilateral process and not to undermine it. A step forward in that direction would be a developing a WTO Action Plan on Regionalism.